In vivo total or partial hepatectomy followed by ex vivo liver resection and autotransplantation for malignant tumors: a single center experience - Xu, Shaoyan; Hu, Chenlu; Jiang, Zedong; Li, Guogang; Zhou, Bo; Gao, Zhenzhen; Wang, Weilin; Yan, Sheng (Frontiers in Oncology, 2023)
Background: Ex vivo liver resection and autotransplantation (ELRAT) may provide an opportunity for R0 resection of conventionally unresectable hepatobiliary cancers and hepatic metastases. To date, few studies of the surgery for malignant tumors have been conducted and there are no known reports of in vivo partial hepatectomy followed by ELRAT (IPH-ELRAT) for malignant tumors. Methods: Between December 2021 and November 2022, ten patients with malignant hepatobiliary primary cancers or hepatic metastases underwent ELRAT at our institution. We shared the surgical skills and postoperative prognoses of these patients were assessed. Results: The types of tumors were biliary tract cancer (BTC, n=8), hepatic metastasis of colonic carcinoma (n=1), and hepatic metastasis of small-bowel stromal tumor (n=1). Five patients underwent in vivo total hepatectomy followed by ex vivo liver resection and autotransplantation (ITH-ELRAT), The other five received in vivo partial hepatectomy followed by ex vivo liver resection and autotransplantation (IPH-ELRAT). Four patients underwent inferior vena cava replacement using artificial blood vessels. The survival rate of all ten patients one month after surgery was 100%. Nine patients (90%) are currently alive, with a median follow-up of 8.5 months (range 6–16.5 months). To date, seven of the nine surviving patients have had no cancer recurrence, including six with BTC. Conclusions: We report the world first five cases that received IPH-ELRAT for malignancies. We also demonstrated relatively favorable outcomes in patients who underwent ELRAT. ELRAT may be a recommendable surgical option for selected patients with conventionally unresectable hepatobiliary malignant tumors.